ADVANCED THERMAL MANAGEMENT FOR A SWITCHED RELUCTANCE MACHINE - Marlow, Richard (My University, 2016)
The thermal management of electric machines is investigated with the application of techniques to a Switched Reluctance Machine and a high-speed Switched Reluctance Machine. Two novel concepts for said management of a Switched Reluctance Machine are proposed and developed: Inter-Laminate Cooling and a Continuous Toroidal Winding. The Inter-Laminate Cooling concept is developed with application to an iron core inductor which serves as a proxy for the electric machine. The experimental results confirmed the capability of the method, expressed by the effectiveness, which defines the performance measure of the applied cooling method; a concept which itself is equally applicable to other cooling methods that may be applied to any electric machine. The effectiveness also describes the gain in allowable input power to the machine which is realized to reach the same thermal limit versus the case without Inter-Laminate Cooling. The Inter-Laminate Cooling was not applied in experimental test to a Switched Reluctance Machine due to the present economic and fabrication limitations. The Continuous Toroidal Winding concept, originally conceived to permit the consideration of a fluid capillary core type of winding to enhance machine cooling, is developed to allow for peripheral cooling of the machine windings and end windings. The Continuous Toroidal Winding version of the Switched Reluctance Machine is investigated for both its thermal and electrical performance in the context of a machine that is equivalent electromagnetically to its conventional counterpart. The Continuous Toroidal Winding Switched Reluctance Machine was found to perform thermally as tested, in a manner superior to that of the conventional machine where the Toroidal machine was simulated and researched at an equivalent level of operation to the conventional machine. The electrical performance of the Toroidal Switched Reluctance Machine although supportive of the simulation analysis used to develop the machine, was not fully conclusive. This may have been due to problematic iron cores used in the construction of the experimental machines. The application of the Inter-Laminate Cooling method to a Switched Reluctance Machine is considered on an analytical basis for the special case of a High Speed Switched Reluctance Machine and found to be of net positive benefit as the machine’s iron losses are dominant over its copper losses. Application of the Inter-Laminate Cooling method to a lower speed machine, whilst beneficial, is not sufficient to significantly impact the temperature of the machine’s windings such that it would offset the loss of specific torque and power. As such, Inter-Laminate Cooling is only applicable where the net benefit is positive overall; in that the gain in input power realized is sufficient to overcome the loss of specific power and torque which will occur due to the increased machine volume. The “effectiveness” and “gain” approach for the evaluation of cooling methods applied to electric machines is a concept which should be adopted to aid in the comparative understanding of the performance of myriad different cooling methods being applied to electric machines both in research and practice, of which there is only minimal understanding.
THERMAL MANAGEMENT FOR A SWITCHED RELUCTANCE MACHINE
Keywords: Toroidal Switched Reluctance Machine; Cooling; SRM; Pyrolytic Graphite Sheet; PGS; Inter Laminate Cooling; ILC; Electric Machine